Tet Methylcytosine Dioxygenase 3 Promotes Cardiovascular Senescence by DNA 5‐Hydroxymethylcytosine‐Mediated Sp1 Transcription Factor Expression - Yanqi Dang; Jing Ma; Shuang Ling; Shurong Wang; Huining Guo; Jun Liu; Guang Ji; Jin‐Wen Xu (MedComm, 2025)
ABSTRACT Cellular senescence is a significant contributor to various age‐related diseases. Tet methylcytosine dioxygenase 3 (TET3) is a pivotal regulator of epigenetic modifications, and this study aimed to elucidate its role in cellular senescence. The study utilized replication and paraquat (PQ)‐induced senescent endothelial cells, as well as TET3 heterozygous, p53 heterozygous, and PQ‐induced senescent mice as experimental models. Senescent endothelial cells were analyzed using hydromethylated DNA immunoprecipitation sequencing, β‐galactosidase staining, real‐time PCR, western blotting, immunofluorescence staining, dot blot, chromatin immunoprecipitation assay, and luciferase reporter assays. These analyses were conducted following TET3 knockdown and gene overexpression. TET3 is instrumental in the elevation of 5‐hydroxymethylcytosine (5‐hmC) levels in both replication and PQ‐induced senescent endothelial cells, as well as in the cardiovascular systems of PQ‐induced aging mice. TET3 significantly promoted cellular senescence in PQ‐induced endothelial cells and mice. TET3 facilitates the upregulation of the Sp1 transcription factor (SP1) through 5‐hmC modification, leading to a synergistic interaction between SP1 and ETS proto‐oncogene 1 that further enhances p53 expression. Moreover, p53 not only promotes cellular senescence in vitro and in vivo but also reciprocally enhances TET3 and 5‐hmC levels. These findings underscore the critical role of elevated TET3 and 5‐hmC levels in cellular senescence.